A sodium ion battery negative electrode sheet and a sodium ion battery
By optimizing the material composition and structure of the negative electrode sheet of sodium ion battery and combining new adhesives and functional polymers, the problems of insufficient flexibility, peeling force and liquid retention rate of the negative electrode sheet are solved, and the cycle life and safety performance of the battery are significantly improved.
Patent Information
- Application Number
- CN202310242904.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-14
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-03-14
AI Technical Summary
The existing sodium ion battery negative electrode sheet has poor flexibility, peeling force and liquid retention rate, resulting in low circulation and safety performance, which cannot meet the needs of high-speed winding production and mass production.
The negative electrode active material layer including hard carbon 90-96%, conductive agent 1-3%, thickener 1-3%, binder 1-4% and liquid retention agent 0.1-0.8% is adopted, combined with the new aqueous polyacrylic acid derivative adhesive and functional polymer SFC, the hard carbon particle size distribution and specific surface area are optimized to improve the flexibility and peel strength of the electrode sheet and effectively lock the electrolyte.
It significantly improves the flexibility, peeling force and liquid retention rate of the negative electrode sheet of sodium ion battery, extends the cycle life of the battery, improves the rate performance and safety performance of the battery, and meets the needs of high-speed winding production and mass production.
Smart Images

Figure CN116314587B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a sodium ion battery negative electrode sheet and a sodium ion battery. Background Art
[0002] As the price of lithium salt fluctuates at a high level, the popularity of sodium-ion batteries as a "replaceable" solution continues to rise. Sodium-ion batteries have broad application prospects in the field of energy storage due to their advantages such as abundant sodium resources, low cost, and good safety performance. For sodium-ion batteries, the negative electrode material plays an important role in loading and releasing sodium ions, which directly affects the overall dynamic performance of the battery, such as rate performance and power density. The existing sodium-ion battery negative electrode sheet has poor peeling force and flexibility, resulting in a low process qualification rate, which cannot meet the needs of high-speed winding and mass production. As the number of cycles increases, coupled with the poor liquid retention capacity of the sodium-ion negative electrode sheet, the electrolyte on the negative electrode surface is continuously consumed and decomposed, and the cycle performance rapidly decreases, resulting in large self-discharge of the manufactured battery cell, severe discharge heat, and even safety problems.
[0003] At present, the negative electrode materials of sodium ion batteries are mainly divided into five types: carbon-based materials, titanium-based materials, alloy materials, organic compounds, and other systems. Carbon-based materials have a better application basis due to their comprehensive cost-performance ratio advantages. According to the microstructure of carbon atoms, carbon-based negative electrodes can be divided into graphite materials, amorphous carbon materials, and nano-carbon materials. Amorphous carbon materials have a higher sodium storage capacity and low cost, and are currently the mainstream choice of negative electrode materials.
[0004] Amorphous carbon is divided into hard carbon and soft carbon. Due to its large specific surface area, more binder needs to be added to ensure the adhesion between the active material and the electrode. This makes the proportion of active material added low, leading to problems such as rising costs and low energy density. In addition, as the number of cycles of the negative electrode increases, the electrolyte on the surface of the electrode is gradually consumed, resulting in a sharp deterioration in the cycle performance.
[0005] In view of this, it is indeed necessary to provide a technical solution to the above problems. Summary of the invention
[0006] In view of the problems existing in the related art, the purpose of this application is to provide a sodium ion battery negative electrode sheet, which significantly improves the flexibility, peeling force and liquid retention rate of the electrode sheet, and solves the problem of reduced cycle performance and safety performance of the electrode sheet due to electrolyte consumption.
[0007] In order to achieve the above object, the present invention adopts the following technical solution:
[0008] According to one aspect of the present application, the present application provides a sodium ion battery negative electrode sheet, comprising:
[0009] Anode current collector;
[0010] A negative electrode active material layer is coated on at least one surface of the negative electrode current collector; the negative electrode active material layer comprises the following composition in weight percentage: 90-96% hard carbon, 1-3% conductive agent, 1-3% thickener, 1-4% binder, and 0.1-0.8% liquid retaining agent;
[0011] The hard carbon particle size distribution D50 (μm), tap density A (g / cm 3 ) and specific surface area B(m 2 / g) satisfies the following relationship:
[0012] 3.0≤D50≤9.0, 0.1<A / B<1.
[0013] Preferably, the hard carbon particle size distribution D50 is 5.0≤D50≤7.0μm, and the tap density A≥0.9g / cm 3 , specific surface area B>2.5m 2 / g.
[0014] Preferably, the conductive agent includes at least one of carbon black, acetylene black, Ketjen black, carbon nanotubes, carbon fibers and graphene.
[0015] Preferably, the binder is at least one of a water-based polyacrylic acid derivative adhesive (PAAd), a styrene-butadiene rubber emulsion, and a polytetrafluoroethylene emulsion.
[0016] Preferably, the thickener is sodium carboxymethyl cellulose (CMC).
[0017] Preferably, the liquid retaining agent is a functional polymer SFC.
[0018] Preferably, the peel strength of the negative electrode sheet is D (N / m), wherein 15.0<D<22.5.
[0019] Preferably, the surface resistance of the negative electrode sheet is E (mΩ), wherein 0.90<E<1.50.
[0020] According to another aspect of the present application, the present application also provides a sodium ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the negative electrode sheet is the above-mentioned sodium ion battery negative electrode sheet.
[0021] Preferably, the wetting angle of the electrolyte is θ, wherein 41°<θ<55°.
[0022] Compared with the prior art, the technical solution provided by this application can at least achieve the following beneficial effects:
[0023] The negative electrode sheet binder of the present application adopts a new type of water-based polyacrylic acid derivative binder (PAAd), the carboxyl content in its structure is higher than CMC, and it can form a strong hydrogen bond with the active material containing hydroxyl groups on the surface, promote the formation of a more uniform coating on the electrode surface than CMC, and can improve the adhesion between the binder and the hard carbon particles, between the hard carbon particles and the substrate, and improve the flexibility and peeling strength of the electrode sheet. The hard carbon particles and the substrate also have strong adhesion, which can provide a stable sodium storage space for sodium ions to escape from the positive electrode; and the functional polymer SFC is added to the electrode sheet formula of the present invention, and the anionic macromolecules therein have an affinity with the electrolyte on the surface of the electrode sheet, which can effectively lock the electrolyte. The present application solves the problem of low battery cycle performance and safety performance due to poor flexibility, peeling force and liquid retention rate of the electrode sheet. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0025] Figure 1 This is a graph showing the peeling strength test data of the negative electrode sheets of the sodium ion battery of Examples 1 to 4 of the present application.
[0026] Figure 2 This is a test data chart of the liquid absorption rate of the negative electrode of the sodium ion battery in Examples 1 to 4 of the present application.
[0027] Figure 3 This is a graph of the negative electrode sheet resistance test data of the sodium ion battery of Examples 1 to 4 of the present application.
[0028] Figure 4 This is a graph of the cycle performance test data of the sodium ion battery negative electrode sheets of Examples 1 to 4 of the present application. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0030] According to one aspect of the present application, the present application provides a sodium ion battery negative electrode sheet, comprising:
[0031] Negative electrode current collector: The current collector is carbon-coated aluminum foil. After the surface of the aluminum foil is carbon-coated, the carbon-coated layer can act as a bridge, tightly bonding the negative electrode active material to the aluminum foil, embedding the particles into each other, thereby improving the conductivity of the negative electrode sheet and ultimately reducing the internal resistance of the battery. In addition, the carbon-coated layer can make the surface of the aluminum foil evenly concave and convex, increasing the contact area between the active material in the electrolyte and the negative electrode current collector, so that when charging and discharging with large currents, electrons can be transferred faster and current can be collected, which can improve the battery rate performance and charge and discharge performance;
[0032] A negative electrode active material layer is coated on at least one surface of the negative electrode current collector; the negative electrode active material layer comprises the following components in weight percentage: 90-96% hard carbon, 1-3% conductive agent, 1-3% thickener, 1-4% binder, and 0.1-0.8% liquid retaining agent;
[0033] The content of the components in the negative electrode active material layer can be adjusted according to the performance requirements. For example, the hard carbon can be 90%, 91%, 92%, 93%, 94%, 96%; the conductive agent can be 1%, 1.5%, 2%, 2.5%, 3%; the thickener can be 1%, 1.5%, 2%, 2.5%, 3%; the binder can be 1%, 1.5%, 2%, 2.5%, 3%, 4%; the liquid retaining agent can be 0.1%, 0.3%, 0.5%, 0.6%, 0.8%;
[0034] The hard carbon particle size distribution D50 (μm), tap density A (g / cm 3 ) and specific surface area B(m 2 / g) satisfies the following relationship:
[0035] 3.0≤D50≤9.0, 0.1<A / B<1, the sodium ion battery made of hard carbon that satisfies this relationship has higher cycle performance and rate performance.
[0036] In one embodiment of the present application, the hard carbon particle size distribution D50 is 5.0-7.0 μm, and the tap density A is ≥ 0.9 g / cm 3 , specific surface area B>2.5m 2 / g, preferably, the tap density is 0.9g / cm 3 ≤A≤2.5g / cm 3 , with a specific surface area of 2.5m 2 / g<B<9m 2 / g. This kind of hard carbon has a small particle size, large specific surface area, high tap density and high conductivity, which is conducive to the rapid deintercalation of sodium ions during discharge, improving the rate performance of sodium ion batteries. Because the crystal arrangement inside the hard carbon structure is disordered, there are many pores, and sodium can be stored between graphite sheets, in closed micropores, on the surface and in defect sites, it also has high isotropy, which enables sodium ions to be embedded and removed from all angles, greatly improving the rate performance and cycle life.
[0037] In one embodiment of the present application, the conductive agent includes at least one of carbon black, acetylene black, Ketjen black, carbon nanotubes, carbon fibers and graphene. A certain amount of conductive agent is added during the production of the electrode to increase the conductivity of electrons and sodium ions, and to accelerate the electron transfer rate by forming a conductive network on the surface of the active material. At the same time, it can absorb and retain the electrolyte, providing more electrolyte interfaces for sodium ions, thereby improving the battery charging efficiency and cycle life.
[0038] In one embodiment of the present application, the binder is at least one of an aqueous polyacrylic acid derivative binder, a styrene-butadiene rubber emulsion, and a polytetrafluoroethylene emulsion. The aqueous polyacrylic acid derivative binder (PAAd) is produced by Fujian Blue Ocean Black Stone New Materials Technology Co., Ltd. and has the following advantages: 1) It hardly swells in the electrolyte, and the electrode sheet structure is stable during the charge and discharge process; 2) The carboxyl content in its structure is higher than that of CMC, and it can form a stronger hydrogen bond with the active material containing hydroxyl groups on the surface, thereby promoting a more uniform coating on the electrode surface than CMC; 3) It can form a denser film in the electrode sheet, increasing the electrical contact between the active material and the current collector; 4) It can improve the adhesion between the binder and the hard carbon particles, and between the hard carbon particles and the substrate, improve the flexibility of the electrode sheet, and thus improve the manufacturing and processing capabilities of the electrode sheet.
[0039] In one embodiment of the present application, the thickener is sodium carboxymethyl cellulose (CMC).
[0040] In one embodiment of the present application, the liquid retaining agent is a functional polymer SFC, which is produced by Shanghai Daoying Industrial Co., Ltd. It is a large-particle anionic polymer emulsion, which is mainly of great significance in improving the liquid retention performance of the battery, the wetting performance of the electrode, improving high-temperature storage, high-temperature circulation, and reducing the internal resistance of the battery.
[0041] In one embodiment of the present application, the peel strength of the negative electrode sheet is D (N / m), wherein 15.0<D<22.5, for example, D can be 15.0 N / m, 17.0 N / m, 19.0 N / m, 21.0 N / m, or 22.5 N / m.
[0042] In one embodiment of the present application, the surface resistance of the negative electrode sheet is E (mΩ), wherein 0.90<E<1.50, for example, E can be 0.90mΩ, 0.96mΩ, 1.10mΩ, 1.30mΩ, or 1.50mΩ.
[0043] According to another aspect of the present application, the present invention also provides a sodium ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the negative electrode sheet is the above-mentioned sodium ion battery negative electrode sheet.
[0044] Among them, the positive electrode sheet uses N-methylpyrrolidone (NMP) as a solvent to prepare an active material slurry, and a conductive agent binder is added and stirred to form a positive electrode slurry, which is then made into a pole sheet through processes such as coating and drying.
[0045] The isolation film is made of at least one of polypropylene film, polyethylene film, polyester substrate and polyacrylonitrile.
[0046] The electrolyte includes sodium salt, carbonate solvent and additive. The carbonate solvent includes cyclic carbonate solvent and chain carbonate solvent; the sodium salt is at least one of NaPF6, NaClO4, NaBF4, NaFSI, NaTFSI, NaSO3CF3 and Na(CH3)C6H4SO3; the additive includes a first additive and a second additive, the first additive is fluoroethylene carbonate or difluoroethylene carbonate, and the second additive is at least one of fluorocyclotriphosphazene, hexafluorocyclotriphosphazene, pentafluoroethoxycyclotriphosphazene and pentafluorophenoxycyclotriphosphazene.
[0047] In one embodiment of the present application, the wetting angle of the electrolyte is θ, wherein 41°<θ<55°; for example, θ can be 41°, 43°, 45°, 48°, 50°, 52°, or 55°.
[0048] The technical solution and beneficial effects of the present application will be described in detail below with reference to specific embodiments and comparative examples.
[0049] Example 1
[0050] This embodiment provides a sodium ion battery negative electrode sheet, comprising:
[0051] Negative electrode current collector carbon-coated aluminum foil;
[0052] The negative electrode active material layer is coated on at least one surface of the negative electrode current collector carbon-coated aluminum foil; the negative electrode active material layer comprises the following composition in weight percentage: 94.3% hard carbon, 1.5% conductive agent, 1.4% thickener, 2.5% binder, and 0.3% liquid retaining agent;
[0053] The hard carbon particle size distribution D50 (μm), tap density A (g / cm 3) and specific surface area B(m 2 / g) must satisfy the following relationship: 3.0≤D50≤9.0, 0.1<A / B<1; preferably, the hard carbon particle size distribution D50 is 5.0≤D50≤7.0μm, and the tap density A≥0.9g / cm 3 , specific surface area B>2.5m 2 / g.
[0054] Wherein, the preparation method of the negative electrode sheet of the sodium ion battery is:
[0055] The negative electrode active material hard carbon, conductive agent carbon black, thickener CMC, binder PAAd, and liquid retaining agent SFC are mixed with solvent N-methylpyrrolidone and pure water in a mass ratio of 94.3%, 1.5%, 1.4%, 2.5% and 0.3% respectively to form a negative electrode slurry, and the negative electrode slurry is coated on the surface of the current collector carbon-coated aluminum foil, and then rolled, cut and made into a negative electrode sheet.
[0056] The negative electrode sheet is matched with a positive electrode sheet, a separator and an electrolyte according to conventional processes to prepare a sodium ion battery.
[0057] Example 2
[0058] The difference from Example 1 is the preparation of the negative electrode sheet.
[0059] The negative electrode active material hard carbon, conductive agent acetylene black, thickener CMC, binder styrene butadiene rubber latex SBR, and liquid retaining agent SFC are mixed with solvent N-methylpyrrolidone and pure water in mass proportions of 93.3%, 1.7%, 1.4%, 2.4% and 0.4% to form a negative electrode slurry, and the negative electrode slurry is coated on the surface of the current collector carbon-coated aluminum foil, and then rolled, cut and sliced to form a negative electrode sheet.
[0060] The rest is the same as in Example 1 and will not be described in detail here.
[0061] Example 3
[0062] The difference from Example 1 is the preparation of the negative electrode sheet.
[0063] The negative electrode active material hard carbon, conductive agent carbon nanotubes, thickener CMC, binder polytetrafluoroethylene emulsion (PTFE), and liquid retaining agent SFC are mixed with solvent N-methylpyrrolidone and pure water in mass proportions of 94.6%, 1.4%, 1.3%, 2.5% and 0.3% to form a negative electrode slurry, and the negative electrode slurry is coated on the surface of the current collector carbon-coated aluminum foil, and then rolled, cut and sliced to form a negative electrode sheet.
[0064] The rest is the same as in Example 1 and will not be described in detail here.
[0065] Example 4
[0066] The difference from Example 1 is the preparation of the negative electrode sheet.
[0067] The negative electrode active material hard carbon, conductive agent graphene, thickener CMC, binder PAAd, and liquid retaining agent SFC are mixed with solvent N-methylpyrrolidone and pure water in mass proportions of 94.3%, 1.5%, 1.4%, 2.5%, and 0.3%, respectively, to form a negative electrode slurry. The negative electrode slurry is coated on the surface of the current collector carbon-coated aluminum foil, and then rolled, cut, and sliced to form a negative electrode sheet.
[0068] The rest is the same as in Example 1 and will not be described in detail here.
[0069] Example 5
[0070] The difference from Example 1 is the preparation of the negative electrode sheet.
[0071] The negative electrode active material hard carbon, conductive agent acetylene black, thickener CMC, binder styrene butadiene rubber latex SBR, and liquid retaining agent SFC are mixed with solvent N-methylpyrrolidone and pure water in mass proportions of 90.5%, 1.8%, 2.0%, 1.9% and 0.5% to form a negative electrode slurry, and the negative electrode slurry is coated on the surface of the current collector carbon-coated aluminum foil, and then rolled, cut and sliced to form a negative electrode sheet.
[0072] The rest is the same as in Example 1 and will not be described in detail here.
[0073] Example 6
[0074] The difference from Example 1 is the preparation of the negative electrode sheet.
[0075] The negative electrode active material hard carbon, conductive agent carbon black, thickener CMC, binder styrene butadiene rubber latex SBR, and liquid retaining agent SFC are mixed with solvent N-methylpyrrolidone and pure water in mass proportions of 93.5%, 1.6%, 1.8%, 2.8% and 0.3% to form a negative electrode slurry, and the negative electrode slurry is coated on the surface of the current collector carbon-coated aluminum foil, and then rolled, cut and sliced to form a negative electrode sheet.
[0076] The rest is the same as in Example 1 and will not be described in detail here.
[0077] Example 7
[0078] The difference from Example 1 is the preparation of the negative electrode sheet.
[0079] The negative electrode active material hard carbon, conductive agent carbon fiber, thickener CMC, binder PAAd, and liquid retaining agent SFC are mixed with solvent N-methylpyrrolidone and pure water in mass proportions of 92.1%, 1.2%, 1.6%, 3.0% and 0.5% to form a negative electrode slurry, and the negative electrode slurry is coated on the surface of the current collector carbon-coated aluminum foil, and then rolled, cut and sliced to form a negative electrode sheet.
[0080] The rest is the same as in Example 1 and will not be described in detail here.
[0081] Example 8
[0082] The difference from Example 1 is the preparation of the negative electrode sheet.
[0083] The negative electrode active material hard carbon, conductive agent carbon nanotubes, thickener CMC, binder styrene butadiene rubber latex SBR, and liquid retaining agent SFC are mixed with solvent N-methylpyrrolidone and pure water in mass proportions of 94.6%, 1.8%, 2.3%, 3.2% and 0.4% to form a negative electrode slurry, and the negative electrode slurry is coated on the surface of the current collector carbon-coated aluminum foil, and then rolled, cut and sliced to form a negative electrode sheet.
[0084] The rest is the same as in Example 1 and will not be described in detail here.
[0085] Example 9
[0086] The difference from Example 1 is the preparation of the negative electrode sheet.
[0087] The negative electrode active material hard carbon, conductive agent graphene, thickener CMC, binder PAAd, and liquid retaining agent SFC are mixed with solvent N-methylpyrrolidone and pure water in mass proportions of 94.3%, 1.6%, 1.9%, 2.3%, and 0.5%, respectively, to form a negative electrode slurry. The negative electrode slurry is coated on the surface of the current collector carbon-coated aluminum foil, and then rolled, cut, and sliced to form a negative electrode sheet.
[0088] The rest is the same as in Example 1 and will not be described in detail here.
[0089] Example 10
[0090] The difference from Example 1 is the preparation of the negative electrode sheet.
[0091] The negative electrode active material hard carbon, conductive agent acetylene black, thickener CMC, binder styrene butadiene rubber latex SBR, and liquid retaining agent SFC are mixed with solvent N-methylpyrrolidone and pure water in mass proportions of 91.5%, 1.3%, 1.7%, 3.1% and 0.3% to form a negative electrode slurry, and the negative electrode slurry is coated on the surface of the current collector carbon-coated aluminum foil, and then rolled, cut and sliced to form a negative electrode sheet.
[0092] The rest is the same as in Example 1 and will not be described in detail here.
[0093] Embodiment 11
[0094] The difference from Example 1 is the preparation of the negative electrode sheet.
[0095] The negative electrode active material hard carbon, conductive agent carbon fiber, thickener CMC, binder styrene butadiene rubber latex SBR, and liquid retaining agent SFC are mixed with solvent N-methylpyrrolidone and pure water in mass proportions of 96.0%, 2.2%, 1.6%, 1.5% and 0.2% to form a negative electrode slurry, and the negative electrode slurry is coated on the surface of the current collector carbon-coated aluminum foil, and then rolled, cut and sliced to form a negative electrode sheet.
[0096] The rest is the same as in Example 1 and will not be described in detail here.
[0097] Example 12
[0098] The difference from Example 1 is the preparation of the negative electrode sheet.
[0099] The negative electrode active material hard carbon, conductive agent carbon black, thickener CMC, binder PAAd, and liquid retaining agent SFC are mixed with solvent N-methylpyrrolidone and pure water in mass proportions of 95.2%, 2.2%, 1.8%, 1.5%, and 0.5%, respectively, to form a negative electrode slurry. The negative electrode slurry is coated on the surface of the current collector carbon-coated aluminum foil, and then rolled, cut, and sliced to form a negative electrode sheet.
[0100] The rest is the same as in Example 1 and will not be described in detail here.
[0101] The sodium ion batteries obtained in Examples 1 to 4 were subjected to electrochemical performance tests. The experimental results are shown in the attached Figure 1-4 shown.
[0102] Depend on Figure 1 It can be seen that compared with other embodiments, the negative electrode sheet peel strength of embodiment 1 is 22.3N / m, which is the best. The negative electrode sheet binder used in embodiment 1 is a new water-based polyacrylic acid derivative binder (PAAd), the carboxyl content in its structure is higher than CMC, and it can form a strong hydrogen bond with the active material containing hydroxyl groups on the surface, promoting the formation of a more uniform coating on the electrode surface than CMC. It can improve the adhesion between the binder and the hard carbon particles, and between the hard carbon particles and the substrate, and improve the flexibility and peel strength of the electrode sheet.
[0103] Depend on Figure 2It can be seen that the wetting angles θ of the negative electrode sheet of the present invention and other embodiments when titrating the same electrolyte are 42.1°, 43.8°, 45.4° and 53.7° respectively, and the wetting angle in embodiment 1 is the smallest. The smaller the wetting angle, the better the liquid absorption effect of the electrode sheet, which is more beneficial to the cycle life of the battery cell. This is mainly due to the addition of functional polymer SFC in the electrode sheet formula of the present invention, in which the anionic macromolecules have an affinity with the electrolyte on the surface of the electrode sheet and can effectively lock the electrolyte.
[0104] Depend on Figure 3 It can be seen that the surface resistance of the negative electrode of the present invention and other embodiments are 0.96mΩ, 1.17mΩ, 1.23mΩ and 0.98mΩ respectively. The surface resistance of the electrode is affected by factors such as active materials, conductive agents, binders, foils and compaction. The smaller the resistance, the smaller the resistance is to the current during the charge and discharge process. Except for the difference in binder, the negative electrode sheets of the present invention and other embodiments are consistent in all other conditions. The resistance of the electrode sheet using the new water-based polyacrylic acid derivative adhesive (PAAd) as the binder is significantly smaller than the resistance of the electrode sheets with other binders. This is mainly due to the higher modulus of acrylic copolymers and the higher interaction force with hard carbon particles, which can effectively connect the hard carbon to the foil and effectively reduce the surface resistance of the electrode sheet.
[0105] Depend on Figure 4 It can be seen that the capacity retention rates of the battery made of the electrode of the present invention after 1500 cycles are 93.40%, 90.29%, 86.66% and 83.87% respectively. Among them, the cycle performance of Example 1 is the best, mainly for the following two reasons: First, the negative electrode binder adopts a new water-based polyacrylic acid derivative adhesive (PAAd), even in the cycle process, the hard carbon particles and the substrate have strong adhesion, which can provide a stable sodium storage space for sodium ions to escape from the positive electrode; second, the formula of the negative electrode contains a functional polymer liquid retaining agent SFC, which can effectively lock the electrolyte on the surface of the electrode through the intermolecular force, providing stable conditions for electronic conduction between the positive and negative electrodes.
[0106] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.
Claims
1. A sodium ion battery negative electrode sheet, characterized in that: include: Anode current collector; A negative electrode active material layer is coated on at least one surface of the negative electrode current collector; the negative electrode active material layer comprises the following components in weight percentage: 90-96% hard carbon, 1-3% conductive agent, 1-3% thickener, 1-4% binder, and 0.1-0.8% liquid retainer; wherein the binder is an aqueous polyacrylic acid derivative binder, and the liquid retainer is a functional polymer SFC; The particle size distribution D50, tap density A and specific surface area B of the hard carbon satisfy the following relationship: 3.0≤D50≤9.0, 0.1<A / B<1; The peel strength of the negative electrode sheet is D, where 15.0<D<22.5, and the surface resistance of the negative electrode sheet is E, where 0.90<E<1.50; The unit of the particle size distribution D50 is μm, and the unit of the tap density A is g / cm 3 The unit of the specific surface area B is m 2 / g, the unit of the peel strength D is N / m, and the unit of the surface resistance E is mΩ.
2. The negative electrode sheet for a sodium ion battery according to claim 1, characterized in that: The particle size distribution D50 of the hard carbon is 5.0≤D50≤7.0μm, and the tap density A≥0.9g / cm 3 , specific surface area B>2.5m 2 / g.
3. The negative electrode sheet for a sodium ion battery according to claim 1, characterized in that: The conductive agent includes at least one of carbon black, acetylene black, Ketjen black, carbon nanotubes, carbon fibers and graphene.
4. The negative electrode sheet for a sodium ion battery according to claim 1, characterized in that: The thickener is sodium carboxymethyl cellulose.
5. A sodium ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, characterized in that: The negative electrode sheet is the negative electrode sheet for a sodium ion battery according to any one of claims 1 to 4.
6. The sodium ion battery according to claim 5, characterized in that: The wetting angle of the electrolyte is θ, wherein 41°<θ<55°.
Citation Information
Patent Citations
Negative electrode slurry and preparation method thereof, negative electrode plate and secondary battery
CN113964309A
Sodium ion battery
CN115458798A